The Effect Of Self-Actualization And Appreciation On The Work Performance Of Employees Of The Bengkulu City Atr/Bpn Office - Anggraini, Sari; Cahya Susena, Karona; Rahman, Abdul (Utami Publisher, 2024)
This study aims to determine the influence of self-actualization and appreciation on the work performance of employees of the ATR/BPN Office of Bengkulu City. This type of research is correlational, which is a study to find out the influence and level of influence between two or more variables without any effort to influence these variables. The method used in collecting data for this study is data collection by conducting direct research on the company ATR/BPN Office of Bengkulu City which is the object of this research by filling out a questionnaire. As a variable measuring tool in the questionnaire, a Likert scale model was used.The sample in this study was 94 people. The results of the study showed that self-actualization (X1) on the work performance of employees (Y) of the ATR/BPN Office of Bengkulu City with a tsig value of < α (0.001<0.05) and a ttable > tcal value (2.571> 1.68195) From the significance value obtained that the X1 variable had a negative effect on employee work performance (Y). The award variable (X2) on the work performance of employees (Y) of the ATR/BPN Office of Bengkulu City with a tsig value < α (0.004<0.05) and a ttable > tcount value (2.571> 1.68195) had a negative effect on employee work performance (Y). The value of Fsig < α 0.05 and Fcal > F table (16.373>2.83) so that it can be concluded that together the independent variable has a negative effect on the dependent variable.